2014
DOI: 10.1097/sla.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery for Esophagectomy

Abstract: ERAS in principle seems logical and safe for esophagectomy. However, the underlying evidence is poor and lacking. Despite this, a number of recommendations for practice and research can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(78 citation statements)
references
References 164 publications
(127 reference statements)
0
69
0
3
Order By: Relevance
“…Esophageal cancer has always been associated with a poor survival, but over the past decades the survival rate for patients undergoing surgery has significantly improved with the introduction of neoadjuvant chemoradiotherapy [1][2][3]. Improved perioperative care, the implementation of enhanced recovery programs and the introduction of minimally invasive techniques, have further contributed to a reduced postoperative mortality and morbidity [4][5][6][7][8]. With these improvements and an increase in survival rates, patients' quality of life and long-term sequelae-such as development of micronutrient deficiencies-of this intensive treatment are becoming more relevant [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer has always been associated with a poor survival, but over the past decades the survival rate for patients undergoing surgery has significantly improved with the introduction of neoadjuvant chemoradiotherapy [1][2][3]. Improved perioperative care, the implementation of enhanced recovery programs and the introduction of minimally invasive techniques, have further contributed to a reduced postoperative mortality and morbidity [4][5][6][7][8]. With these improvements and an increase in survival rates, patients' quality of life and long-term sequelae-such as development of micronutrient deficiencies-of this intensive treatment are becoming more relevant [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for ERAS in oesophageal surgery is poor; in a recent systematic review, Findlay et al identified only eight retrospective series with a total of 1127 patients. These were predominantly reports of single surgeon series and open resections 4. In some units, one surgeon but not others have embraced ERAS for oesophageal surgery5, and in other units, only the fittest patients have been included, making the overall benefits hard to establish 6…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal pain management is a recognized risk factor for respiratory complications after transthoracic esophagectomy 1. Thoracic epidural analgesia (TEA) is the current gold-standard analgesia in these patients and is an important component of the fast-track programs 24. However, TEA cannot always be performed and other strategies of pain relief need to be considered in select patients.…”
Section: Introductionmentioning
confidence: 99%